Cardiovascular risk factors among 15-20 years old rural subjects residing in Dikgale Demographic Surveillance Site (DDSS), Limpopo Province - Phoku, Nkosinathi Terrence (University of Limpopo (Turfloop Campus), 2013)
Cardiovascular diseases (CVDs) are among one of the well documented conditions and pose a significant health burden in the world as they areconsidered to be of adult onset. However, recent studies have shown that in developed countries CVD risk factors are becoming prevalent in young people which isof great concern. Therefore, the aim of this study was to determine if CVD risk factors are present in young subjects aged 15-20 years of age residing in a rural area of a developing country. Methods: Subjects aged between 15-20 years who participated in the “Gene - Environment interaction project” were included in this sub-study. Total cholesterol, triglycerides, HDL-cholesterol, LDLcholesterol, insulin, glucose, creatinine, Lp(a), apoB, apoA-1 and hs-CRPwere determined. Blood pressure, physical activity (number of steps/day), weight, height, waist circumference and hip circumference were obtained from the database. Subjects with CRP levels above 10mg/L and creatinine levels above 130 mmol/L were excluded. Results: The present study showed an overall high prevalence of some CVD risk factors. There was high prevalence of insulin resistance (23.0% in females and 34.7% in males), and high hs-CRP (18.4% in females, 12.9% in males). The prevalence of low HDL-C levels was high (55.2% in females and 16.8 % in males), however, the prevalence of abnormal levels of other lipids such as total cholesterol/HDL-cholesterol ratio was low in both males and females. The prevalence of an increased apoB/apoA ratio was significantly higher in females 26.4% compared to males 7.9%. The prevalence of overweight (12.6%) and obesity (9.2%) was higher in females than in males (overweight 1%, obesity 0 %). The prevalence of hypertension was comparable between the two genders (5.7% in females and 10.9 % in males). Conclusion: The results showed a relatively high prevalence of non-traditional risk factors for cardiovascular diseases in adolescents residing in a rural area, Limpopo Province, while the prevalence of traditional risk factors such as total cholesterol and triglycerides was low.
Thesis (M.Sc. (Chemical Pathology) --University of Limpopo, 2013
Keywords: Cardiovascular diseases; Heart diseases; 616.12; Heart failure; Heart -- Diseases; Cytodiagnosis